Fatigue Behaviour of the Novel Titanium Alloys TIMETAL® 407 and TIMETAL® 412 - WILLIAM DAVEY (2021)
TIMETAL®407 (Ti-407) is a medium strength (~650MPa 0.2%YS) titanium alloy, recently developed by TIMET, in conjunction with Rolls-Royce plc for use in applications requiring high energy absorption at impact. Preliminary Charpy Impact (V notch) testing showed Ti-407 to absorb nearly twice the impact energy of Ti-6-4 and exhibit more than 2.5 times the lateral expansion. Further initial testing suggested the high cycle fatigue (HCF) run out stress of Ti-407 matches that of Ti-6-4 and other high strength alpha-beta titanium alloys. Ti-407 displayed more than double the tool life than that of Ti-6-4. The reduction in tool wear supports lower forces required for faster, more efficient machining. Compared to Ti-6-4, the relatively low elevated temperature flow stress, greater malleability and wide process window should allow Ti-407 to be processed with fewer reheats, while exhibiting reduced surface cracking and giving a consistently good surface finish. Optimised Ti-407 manufacturing processes should allow parts to be formed closer to net shape giving higher yields and requiring less machining to the components finished size. This project has evaluated HCF, as well as low cycle fatigue (LCF) and dwell fatigue crack initiation mechanisms in Ti-407, to clarify the effects of alloy chemistry, microstructural morphology and scale, and crystallographic texture. A derivative of Ti-407, Ti-412 (~750MPa 0.2%YS) was also tested towards the end of the project and helped to further elucidate understanding of the fatigue characteristics of the two alloys. Of interest was the strong HCF response displayed relative to the monotonic tensile strength. As well as the investigation into the crack initiation mechanisms, an assessment of crack propagation across a range of microstructural conditions was carried out on Ti-407 material.